2008
DOI: 10.1111/j.1742-6723.2008.01085.x
|View full text |Cite
|
Sign up to set email alerts
|

Mass gathering medicine: The Melbourne 2006 Commonwealth Games experience

Abstract: The majority of first-aid presentations during the M2006 were of low acuity and treatment resulted in return of patrons to the event, with only a small number requiring ambulance transport to hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…One study reported a positive correlation of heat index with the rate for medical use during an event. 18 Several studies suggested heat-related illness as a major issue in mass-gathering events, but it only represented 1%-12% of the cases; this could have been under diagnosis of heat exhaustion with headache. 10 This indicates that extremes of weather are contributors to higher rates of medical use, confirming the findings of Milstein and colleagues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported a positive correlation of heat index with the rate for medical use during an event. 18 Several studies suggested heat-related illness as a major issue in mass-gathering events, but it only represented 1%-12% of the cases; this could have been under diagnosis of heat exhaustion with headache. 10 This indicates that extremes of weather are contributors to higher rates of medical use, confirming the findings of Milstein and colleagues.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] This review did not include any medical records or review of personal health information. The research period was started in 2003 because the publication date of the last review on interventions during mass gatherings was the previous year; however, the scope of the review was more narrow as only articles that reported data on noncommunicable health issues were only included.…”
Section: Review Designmentioning
confidence: 99%
“…Other past events needed to overstaff and oversupply at each of the venues in preparation to face the worstcase scenario (14,23). However, the TOROC's Medical Service, thanks to the strengthening of the Regional Health System (offering its own personnel operating 24 h a day for the spectators) and the expertise of a preexisting staff, ensured an effective and efficient answer to health needs.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, the 28,536 permanent employees in the Olympic Hospitals supported adequately the TOROC's Medical Service. The overall staff in polyclinics and medical centers corresponded to 934 people (520 in polyclinics and 414 in medical centers) (Figure 1), whereas no less than 1102 medical volunteers served at all venues during the Salt Lake City Winter Olympic Games, and a good 700 volunteer first aiders served during the Melbourne 2006 Commonwealth Games (14,23).…”
Section: Discussionmentioning
confidence: 99%
“…Injuries were the most common health problems in these MGs. 22,26,27,29,50,59,62 Athletes and participants both were affected by injuries in the sport MGs. During the 2004 Olympic games, the most common site of injuries was the thigh, knee, and lumbar spine, respectively.…”
Section: Sport Mgsmentioning
confidence: 99%